Implementation Study of Electronic Medical Records at PT Nusantara Medika Utama: Kajian Implementasi Rekam Medis Elektronik di PT Nusantara Medika Utama - Nanda Adillya Meidyliana; Wiwik Handayani (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
The implementation of Electronic Medical Records (EMR) at PT Nusantara Medika Utama aims to enhance the quality of healthcare services and operational efficiency. This study employs both qualitative and quantitative approaches to explore the benefits and challenges encountered in EMR implementation. Data were collected through interviews with medical staff and surveys of patients, as well as secondary data analysis from hospital reports. The findings indicate a significant increase in service speed, due to medical staff able to access patient records in real-time. Although challenges such as resistance from medical personnel and technological infrastructure issues persist, the results demonstrate that EMR has great potential to improve patient satisfaction and hospital operational efficiency. This research is expected to provide insights for further development in the implementation of EMR systems in the healthcare sector.